PLATELET-RICH PLASMA EFFICACY IN EPISIOTOMY WOUNDS - Fatima Hussain kadhum; Israa Hashim Abid Al-Karim (Western European Studies, 2024)
During vaginal birth, 85% of females suffer from perineal trauma. A major chronic effect of perineal trauma is pain. Prejudice against vaginal birth is the poor life quality and pain. A new treatment for perineal trauma and pain is Platelet rich plasma. The aim of the current research was to find healing advantages of Platelet rich plasma in episiotomy wounds, concerning the time of healing, signs of infection, and intensity of pain. A clinical randomized research was conducted in Tikrit Teaching Hospital, the of Obstetrics and Gynecology Department, in a period between October 2023 untilJune 2024. The women will be randomized into either group of Platelet rich plasma (30 females) or (30 females) group of control. Facts collected through: standard questionnaire contain the information of sociodemographic characteristics, obstetrical History, and medical history. Assessment of wound healing by: visual analogue scale, Edema, Redness, Ecchymosis. scale, approximation, and Scar Scale of Vancouver, at basal day one, 7th , 14 th, and 28th day. The after treatment Vancouver Scar Scale score was significantly lower among group of Platelet rich plasma (0.45±0.2) than group of control (1.3±0.6). The decrement in the Vancouver Scar Scale score was significantly higher among the group of Platelet rich plasma (-1.85) group than the group of control (-1.3). The commonest side effect of Platelet rich plasma was erythema at site of injection 14(46.7%), followed by ecchymosis 4(13.3%) which resolve after 1 week, no cases of infection or dehiscence scare reported. Platelet rich plasma are safe and had good effect on episiotomy wound healing.
Keywords: Platelet-Rich Plasma in Episiotomy; Episiotomy with Platelet-Rich Plasma